Factors Affecting Live Streaming Commerce Purchase Behavior - Felix Leonard Harrianto; Dudi Anandya; Bobby Ardiansyahmiraja (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
Online shopping provides various benefits to customers, but it has a fundamental limitation, which is direct interaction with the product. The growth of live streaming commerce (LSC) is a new way for people to reduce their concerns in online shopping. This study identifies the factors that can influence purchase intention in LSCs. The present study used a quantitative approach. The population of this study is all Indonesians who have shopped in LSC in which a sample of 102 respondents was obtained through online distribution of a questionnaire. The data was analyzed descriptively and through Partial Least Square Structural Equation Modelling (PLS-SEM). The results of this study show that physical characteristic similarity has a significant effect on product fit uncertainty. Value similarity has a significant effect on trust. Access to online information has a significant effect on trust but not purchase intention. Trust has a significant influence on product uncertainty and purchase intention. Likewise, product uncertainty has a significant effect on purchase intention. Price has a significant effect on hedonic motivation but not purchase intention. Hedonic motivation has no significant effect on purchase intention. E-commerce platforms and merchants who utilize LSCs can use the findings in this study to improve their business.Keywords: Live streaming commerce, Product uncertainty, Purchase intention, TikTok